ANALISA PENGUKURAN KINERJA MENGGUNAKAN KEY PERFORMANCE INDICATOR DENGAN PENDEKATAN METODE BALANCED SCORECARD DI. XYZ - Muhammad Rafli (2021)
The globalization of the current era, forcing some or all companies to compete tightly in order to be able to survive the current industrial competition. The purpose of this study is to measure the performance of PT. XYZ uses theapproach Balanced Scorecard. By measuring performance with theapproach, Balanced Scorecard it can find out the actual number of the performance of PT. XYZ by knowing thecriteria Key Performance Indicator and then weighting its priorities with the Analytical Hierarchy Process which later when it has been weighted it can be given suggestions for improvement so that it becomes a lesson and evaluation for PT. XYZ. The results of this study indicate that the highest priority of this company is the Growth and Learning perspective which has a priority weight of 0.39, followed by a financial perspective with a weight of 0.27, then an internal business perspective of 0.20, and the lowest priority value falls on the customer perspective with a value of 0.14. While the performance owned by PT. XYZ in the financial perspective is 0.198, the customer perspective is 0.092, the internal business perspective is 0.136, and the growth and learning perspective is 0.091.